2004
DOI: 10.1175/1525-7541(2004)005<0487:camtpg>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

CMORPH: A Method that Produces Global Precipitation Estimates from Passive Microwave and Infrared Data at High Spatial and Temporal Resolution

Abstract: A new technique is presented in which half-hourly global precipitation estimates derived from passive microwave satellite scans are propagated by motion vectors derived from geostationary satellite infrared data. The Climate Prediction Center morphing method (CMORPH) uses motion vectors derived from half-hourly interval geostationary satellite IR imagery to propagate the relatively high quality precipitation estimates derived from passive microwave data. In addition, the shape and intensity of the precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
1,928
1
49

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,808 publications
(1,988 citation statements)
references
References 24 publications
10
1,928
1
49
Order By: Relevance
“…2018, 10, 1121 4 of 25 ancillary data set that aids users of the V5.0 Aquarius Level 2 data to better understand the salinity stratification changes due to rain. The product uses as input the surface rain rates from the NOAA CMORPH (CPC-Climate Prediction Center-Morphing technique) global precipitation data set [16]. The average instantaneous rain rate is calculated using a structure of 13 CMORPH pixels around the center of the Aquarius IFOV, where the weight associated with each pixel is based on the antenna gain.…”
Section: Rain Rate and Rain Flaggingmentioning
confidence: 99%
“…2018, 10, 1121 4 of 25 ancillary data set that aids users of the V5.0 Aquarius Level 2 data to better understand the salinity stratification changes due to rain. The product uses as input the surface rain rates from the NOAA CMORPH (CPC-Climate Prediction Center-Morphing technique) global precipitation data set [16]. The average instantaneous rain rate is calculated using a structure of 13 CMORPH pixels around the center of the Aquarius IFOV, where the weight associated with each pixel is based on the antenna gain.…”
Section: Rain Rate and Rain Flaggingmentioning
confidence: 99%
“…This dataset, produced by the National Meteorological Information Center of China Meteorological Administration, is used to study the diurnal cycle of precipitation. It combines the National Oceanic and Atmospheric Administration (NOAA)/Climate Prediction Center morphing technique (CMORPH) precipitation data (Joyce et al 2004) and the hourly precipitation dataset observed by more than thirty thousand automatic meteorological stations in China ( Fig. 1) (Shen et al 2010a).…”
Section: Datamentioning
confidence: 99%
“…While real-time precipitation analyses of reasonable quality are available over most of the United States (e.g., McEnery et al 2005), many parts of world lack sufficiently dense radar and rain gauge networks. Satellite-derived global precipitation products provide improved spatial coverage (Huffman et al 2007;Joyce et al 2004), but they are known to exhibit seasonally and spatially dependent biases (Villarini et al 2009;Zeweldi and Gebremichael 2009). Drought classifications from prognostic water balance models (e.g., NLDAS) depend strongly on the assumed model physics, dynamic forcings, and subsurface properties (Mo 2008), requiring information about soil-moisture-holding capacity and retention characteristics that is difficult to obtain with adequate accuracy over large areas.…”
Section: Introductionmentioning
confidence: 99%